1993
DOI: 10.1111/j.1399-302x.1993.tb00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of hemin and Congo red by oral hemolytic spirochetes

Abstract: Colony-forming units or cells in suspension of oral anaerobic spirochetes (Treponema denticola, Treponema vincentii and Treponema socranskii) bind hemin and Congo red. Hemin or Congo red binds to a hydrophobic polypeptide receptor that is located in the outer membrane of the bacterial cells and it has a relative molecular mass of 47 kDa. These oral spirochetes also lyse sheep erythrocytes to produce beta-hemolytic zones around colony-forming units. The oral spirochetes may acquire iron for growth when they lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Although CR-and/or haemin-binding phenotypes have been observed in a number of pathogenic organisms, including A. salmonicida (Kay et al, 1985), enteroinvasive E. coli (Stugard et al, 1989), Neisseria meningitidis (Payne & Finkelstein, 1977), Porphyromonas gingivalis (Genco et al, 1994), Shigella flexneri (Daskaleros & Payne, 1987;Stugard et al, 1989), Treponema species (Scott et al, 1993), Vibrio chlolerae (Payne & Finkelstein, 1977), Yersinia enterocolitica (Prpic et al, 1983) and highly variable pigmented Yersinia pseudotu6erculosis (Burrows, 1973), none of these phenotypes appears to be analogous to the Hms phenotype of Y . pestis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CR-and/or haemin-binding phenotypes have been observed in a number of pathogenic organisms, including A. salmonicida (Kay et al, 1985), enteroinvasive E. coli (Stugard et al, 1989), Neisseria meningitidis (Payne & Finkelstein, 1977), Porphyromonas gingivalis (Genco et al, 1994), Shigella flexneri (Daskaleros & Payne, 1987;Stugard et al, 1989), Treponema species (Scott et al, 1993), Vibrio chlolerae (Payne & Finkelstein, 1977), Yersinia enterocolitica (Prpic et al, 1983) and highly variable pigmented Yersinia pseudotu6erculosis (Burrows, 1973), none of these phenotypes appears to be analogous to the Hms phenotype of Y . pestis.…”
Section: Discussionmentioning
confidence: 99%
“…Haemin-and CR-binding phenotypes serve distinct roles in a variety of pathogens (Daskaleros & Payne, 1987;Gardufio & Kay, 1992;Genco et al, 1994;Kay et al, 1985;Scott et al, 1993); the ability to bind these substrates has been correlated with virulence, but not always with haemin utilization. A long-held hypothesis is that the Hms' phenotype allows Y .…”
Section: Introductionmentioning
confidence: 99%
“…TO identify the components responsible for Congo red binding, whole cells of strain W50 grown in haemin-excess batch culture (at a concentration of 4 mg ml-l) were subjected to various pretreatments as described by Scott et al (1993). These included (a) papain in NaCl/Tris pH 6.5, containing 1.3 mM cysteine hydrochloride; (b) pepsin in 10 mM HC1; (c) trypsin in NaCl/Tris, pH 8.5 ; and (d) proteinase K in NaCl/Tris, pH 7-4.…”
Section: Congo Red Binding To Cells After Various Pretreatmentsmentioning
confidence: 99%
“…denticola does not appear to produce siderophores (45), so it must have other mechanisms for iron acquisition. Indeed, T. denticola can bind lactoferrin (50) and hemin (7,44).…”
mentioning
confidence: 99%
“…In addition, T. denticola produces a hemolysin (6), which could lyse erythrocytes in vivo and provide heme compounds for the bacterium. Previous studies have shown that T. denticola contains at least two hemin binding molecules: a 47-kDa constitutively produced hemin binding protein from strain ATCC 35405 (45) and a 44-kDa hemin binding protein (HbpA), which is up-regulated under iron-restricted growth, that is found in strains GM-1, MS-25, ATCC 33520, and ATCC 33404 (7). However, the role of these proteins in iron acquisition is unproven and the mechanism of binding and iron transport by these proteins has not been characterized.…”
mentioning
confidence: 99%